The Effect of Phytoestrogen Substances on the Morphometry of Reproductive Organs in Increasing the Fertility of Rabbits - Suhrob, Aminov (American Journal of Biomedicine and Pharmacy, 2025)
This article examines the effect of phytoestrogen substances on the morphological and morphometric changes in the reproductive organs of rabbits. During the experiment, differences between the group treated with phytoestrogens and the control group were analyzed. The results showed that phytoestrogen substances positively influence the size, weight, and functional activity of the reproductive organs. This study contributes to determining the potential use of phytoestrogens to improve the reproductive performance of rabbits.